Development of an optimization method for minimizing vibrations of a hydraulic damper. (September 2013) - Czop, Piotr; Sławik, Damian; Wszołek, Grzegorz
The aim of this paper is to provide a mathematical method for minimizing the vibrations produced by hydraulic dampers, while maintaining the same damping force characteristics. The vibration level depends on the force–pressure characteristics of valve systems, which determine the damping force and high-frequency acceleration characteristic of a damper, and which need to be optimally tuned to lower the noise level. The paper considers a model-based approach to obtain the optimal pressure–flow characteristic via simulations conducted with the use of coupled models, including the damper and the servo-hydraulic tester model. The objectives of this work were as follows: (i) develop or adapt a double-tube damper model including pressure–flow valve characteristics; (ii) define key parameters of the valve characteristics influencing the high-frequency piston-rod acceleration, which is considered as a measure of vibration level; (iii) identify the parameter values (trends) minimizing the piston-rod acceleration using two alternative methods, namely a quick-and-dirty method based on a design of experiment (DOE) plan and a nonlinear programming method; (iv) obtain the optimal pressure–flow characteristic minimizing the vibration level by means of simulation; and (v) perform an experimental study comparing the high-frequency content of acceleration produced by the damper assembled with the original and optimized valve system using a laboratory setup.